The effects of whole-body vibration in isolation or combined with strength training in female athletes - Preatoni, E.; Colombo, A.; Verga, M.; Galvani, C.; Faina, M.; Rodano, R.; Preatoni, E.; Cardinale, M (The Journal of Strength and Conditioning Research, 2012)
The aims of this study were to assess the behavior of a vibrating platform under different conditions and to compare the effects of an 8-week periodized training program with whole-body vibration (WBV) alone or in combination with conventional strength training (ST). Vibrating frequencies, displacements, and peak accelerations were tested through a piezoelectric accelerometer under different conditions of load and subjects' position. Eighteen national-level female athletes were assigned to 1 of 3 different groups performing WBV, conventional ST, or a combination of the 2 (WBV + ST). Isometric maximal voluntary contraction, dynamic maximal concentric force, and vertical jump tests were performed before and after the conditioning program. Vibrating displacements and maximum accelerations measured on the device were not always consistent with their expected values calculated from the display and manufacturers' information (sinusoidal waveforms). The WBV alone or in combination with low-intensity resistance exercise did not seem to induce significant enhancements in force and power when compared with ST. It appears that WBV cannot substitute parts of ST loading in a cohort of young female athletes. However, vibration effects might be limited by the behavior of the commercial platforms as the one used in the study. More studies are needed to analyze the performances of devices and the effectiveness of protocols.